2020
DOI: 10.1002/agg2.20008
|View full text |Cite
|
Sign up to set email alerts
|

The sorghum epicuticular wax locus Bloomless2 reduces plant damage in P898012 caused by the sugarcane aphid

Abstract: The sugarcane aphid [Melanaphis sacchari] has been rapidly spreading in the southern United States with devastating impacts on sorghum [Sorghum bicolor (L.) Moench]. Previous studies have shown the sorghum epicuticular wax mutants, in particular a bloomless2 (bm2) mutant and a sparse bloom mutant, were resistant to greenbugs [Schizaphis graminum], a type of aphid. In this study we sought to determine if five different genotypes, which all have mutations in the Bm2 locus, differ for sugarcane aphid resistance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In one example of monogenic constitutive antixenosis, sorghum aphid ( Melanaphis sorghi ; Theobald, 1904) feeding preference was affected in choice‐assays by a bloomless gene knockout, which lacked cuticular wax while reproduction in no‐choice assays did not (Cardona et al., 2022). This trait may be background dependent as a consistent effect on aphid damage was not observed across several different mutant genotypes (Harris‐Shultz et al., 2019). A contrasting example of HPR is the monogenic induced antibiosis phenotype of the cloned Mi‐1 and Vat genes encoding nucleotide binding leucine‐rich repeat (NLR) receptors (Dogimont et al., 2014; Nombela et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In one example of monogenic constitutive antixenosis, sorghum aphid ( Melanaphis sorghi ; Theobald, 1904) feeding preference was affected in choice‐assays by a bloomless gene knockout, which lacked cuticular wax while reproduction in no‐choice assays did not (Cardona et al., 2022). This trait may be background dependent as a consistent effect on aphid damage was not observed across several different mutant genotypes (Harris‐Shultz et al., 2019). A contrasting example of HPR is the monogenic induced antibiosis phenotype of the cloned Mi‐1 and Vat genes encoding nucleotide binding leucine‐rich repeat (NLR) receptors (Dogimont et al., 2014; Nombela et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We found that several beneficial insect species collect sorghum pollen and that sorghum heavily infested by SA greatly increases the abundance and diversity of Hymenoptera. We conducted two studies to (1) identify insects that collect or consume sorghum pollen and determine if the plant height, panicle length and rating date influenced insect [20] and PI 257599 is a sweet, late maturing tall line [21,22] and the F 4 lines were segregating for a large number of traits including plant height, panicle length, and flowering time. The test was planted on a 0.79 ha field, flanked by 149 plots of a (N109A × PI 257599) F 4 population for advancement and only these 149 plots were sprayed with the insecticide Sivanto ® (17.09% flupyradifurone; Bayer Crop Science, Whippany, NJ, USA).…”
Section: Introductionmentioning
confidence: 99%